George Mountford Adie and Joseph Azize, George Adie: A Gurdjieff Pupil in Australia. - Cusack, Carole M. (Journal for the academic study of religion, 2011)
George Mountford Adie and Joseph Azize, George Adie: A Gurdjieff Pupil in Australia. Lighthouse Editions Limited, Cambridge, 2007, pp. xix + 309, ISBN: 978-1-904998-02-0 (Pbk).